2020
DOI: 10.1021/acschemneuro.0c00697
|View full text |Cite
|
Sign up to set email alerts
|

Breviscapine Alleviates Cognitive Impairments Induced by Transient Cerebral Ischemia/Reperfusion through Its Anti-Inflammatory and Anti-Oxidant Properties in a Rat Model

Abstract: Cerebral ischemia/reperfusion (I/R)-induced injury is a common phenomenon of stroke, and the effective treatment for I/R-induced brain tissue damage is limited. Breviscapine has been widely used in China as herbal medicine to treat cardiovascular diseases for hundreds of years and has been demonstrated to possess potent cardiovascular pharmacological effects. This study aims to investigate the neuroprotective effect of breviscapine on cerebral I/R-induced injury. The rat model of middle cerebral artery occlusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Apart from these active components mentioned, there are still many active ingredients that are effective in the treatment of stroke in preclinical studies and are under clinical studies ( Supplementary Table S1 ). For example, breviscapine could alleviate cognitive impairments and neuro defects caused by stroke through its anti-inflammatory and antioxidant, promoting autophagy ( Li et al, 2020 ). Timosaponin B and scutellarein had neuroprotective effects against stroke by their antithrombotic, antiplatelet, and anticoagulation effects ( Dong et al, 2019 ).…”
Section: Traditional Chinese Medicine Therapymentioning
confidence: 99%
“…Apart from these active components mentioned, there are still many active ingredients that are effective in the treatment of stroke in preclinical studies and are under clinical studies ( Supplementary Table S1 ). For example, breviscapine could alleviate cognitive impairments and neuro defects caused by stroke through its anti-inflammatory and antioxidant, promoting autophagy ( Li et al, 2020 ). Timosaponin B and scutellarein had neuroprotective effects against stroke by their antithrombotic, antiplatelet, and anticoagulation effects ( Dong et al, 2019 ).…”
Section: Traditional Chinese Medicine Therapymentioning
confidence: 99%
“…6 It was reported that administration of breviscapine ameliorated CIR-induced neurological injury and improved the neurological performance in MCAO rats through its anti-inflammatory and anti-oxidant properties. 7 Diosmetin is a natural flavonoid compound present in citrus fruit. More notably, diosmetin has been found to play critical roles in ischemia-reperfusion (IR)induced diseases through its antioxidant and anti-inflammatory effects.…”
Section: Introductionmentioning
confidence: 99%
“…Morin alleviated cerebral damage and protected the blood–brain barrier integrity by attenuating oxidative stress, inflammation, and apoptosis in a middle cerebral artery occlusion (MCAO) and reperfusion model 6 . It was reported that administration of breviscapine ameliorated CIR‐induced neurological injury and improved the neurological performance in MCAO rats through its anti‐inflammatory and anti‐oxidant properties 7 . Diosmetin is a natural flavonoid compound present in citrus fruit.…”
Section: Introductionmentioning
confidence: 99%
“…Salvianolic acid D, a polyphenol component of Salvia miltiorrhiza Bunge, inhibits NF-κB activation and inflammatory factor release mediated by HMGB1-TLR4 signaling and attenuates HMGB1-mediated inflammatory response by inhibiting TLR4/MyD88/NF-κB signaling pathway [ 36 ]. Furthormore, other natural compounds such as triptolide, β-patchoulene, ginkgetin, tanshinone IIA, breviscapine, diosgenin, icariin, and berberine can also exert a protective effect against ischemic brain injury by inhibiting the NF-κB signaling pathway [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. The NF-κB signaling pathway and the chemical structure of natural compounds are shown in Figure 2 .…”
Section: The Signaling Pathways Of Active Compounds In the Treatment ...mentioning
confidence: 99%